PERENCANAAN STRUKTUR RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Ahmad Faisol; Saddam Mirza; Nuroji Nuroji; Himawan Indarto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Structure design of Sultan Agung Islamic Hospital designed by SNI 03‒2847‒2002 and SNI 1726‒2012, where analysis of earthquake load structure the building made by Spectrum Analysis Method of Dynamic Response. The analysis dynamic response spectrum of building structure is included in Seismic Design Criteria of type D with high seismicity level of risk, so that the planning system is the method used by the building frame structure configuration bearers Special Moment Frame System(Sway‒special). Sway‒special system is designed to be the building does not collapse during an earthquake in excess of the earthquake that has been designed, therefore Sway‒special the model is designed to qualify the strong column weak beam, where the columns are designed to withstand the beam when the beam undergo plastic hinge. Additionally joint should also be designed to prevent well collapse when the beam experiencing first plastic hinge. The structure design of Sultan Agung Islamic Hospital has asymmetrical shape configuration , so when an earthquake the building will undergo rotational stiffness caused by the center of mass and the center of rigidity is not located in a single point, so that should be dilated so that the center of mass and center of stiffness becomes coincide.